2007
DOI: 10.1214/009053606000001505
|View full text |Cite
|
Sign up to set email alerts
|

Statistical inferences for functional data

Abstract: With modern technology development, functional data are being observed frequently in many scientific fields. A popular method for analyzing such functional data is ``smoothing first, then estimation.'' That is, statistical inference such as estimation and hypothesis testing about functional data is conducted based on the substitution of the underlying individual functions by their reconstructions obtained by one smoothing technique or another. However, little is known about this substitution effect on function… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
235
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 219 publications
(243 citation statements)
references
References 32 publications
8
235
0
Order By: Relevance
“…The L 2 -norm-based test (Faraway 1997;Zhang and Chen 2007) adopted for (1) uses the test statistic S n = T SSR n (t)dt. Under the null hypothesis (1), it can be shown that S n ∼ βχ 2 d approximately, where s, u)γ (u, t)du.…”
Section: (T T)dt Denote the Trace Of γ (S T) The Pooled Sample Covmentioning
confidence: 99%
See 4 more Smart Citations
“…The L 2 -norm-based test (Faraway 1997;Zhang and Chen 2007) adopted for (1) uses the test statistic S n = T SSR n (t)dt. Under the null hypothesis (1), it can be shown that S n ∼ βχ 2 d approximately, where s, u)γ (u, t)du.…”
Section: (T T)dt Denote the Trace Of γ (S T) The Pooled Sample Covmentioning
confidence: 99%
“…5). When the k samples are not Gaussian and when the sample sizes are small, the L 2 -norm-based test and the F-type test are not preferred (see Zhang 2013). In this case, the bootstrap versions of these tests can be used to bootstrap the p-values of S n and F n (see Zhang 2013, p. 159 …”
Section: (T T)dt Denote the Trace Of γ (S T) The Pooled Sample Covmentioning
confidence: 99%
See 3 more Smart Citations